2022
DOI: 10.2147/dddt.s379468
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine Inhibits Orthodontic Tooth Movement and Root Resorption in Rats and Enhances Osteogenic Differentiation of PDLSCs

Abstract: To investigate the effects of sinomenine on orthodontic tooth movement and root resorption in rats, as well as the effect of sinomenine on the osteogenesis of periodontal ligament stem cells (PDLSCs). Methods: Fifty-four male Wistar rats were randomly divided into 3 groups: control group, 20 mg/kg sinomenine group and 40 mg/kg sinomenine group. Fifty-gram orthodontic force was applied to all groups. Each group was injected intraperitoneally with corresponding concentration of sinomenine every day. After 14 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Zhang et al [ 29 ] reported that SIN decreased osteoclast differentiation or activity and reduced bone destruction in breast cancer patients. In a study on the treatment of orthodontic tooth movement and root resorption, Li et al [ 17 ] reported that SIN promoted the osteogenic differentiation of PDLSCs in vitro , but the study failed to further elucidate the specific mechanism by which SIN promotes the osteogenic differentiation of PDLSCs. However, these studies provide useful insight into SIN as a therapeutic option for osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [ 29 ] reported that SIN decreased osteoclast differentiation or activity and reduced bone destruction in breast cancer patients. In a study on the treatment of orthodontic tooth movement and root resorption, Li et al [ 17 ] reported that SIN promoted the osteogenic differentiation of PDLSCs in vitro , but the study failed to further elucidate the specific mechanism by which SIN promotes the osteogenic differentiation of PDLSCs. However, these studies provide useful insight into SIN as a therapeutic option for osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Liao et al [ 16 ] concluded that SIN significantly alleviated arthritis symptoms in mice with collagen-induced arthritis by inhibiting proinflammatory cytokine secretion and inflammatory mediator production by synovial cells in arthritic mice and could decrease the formation, activity and survival of osteoclasts. SIN exerted beneficial therapeutic effects on periodontal erosive diseases and loose teeth both in vitro and in vivo by promoting the osteogenic differentiation of periodontal ligament stem cells (PDLSCs)[ 17 ]. However, there have been no reports on the effects of SIN in the treatment of osteoporosis, especially the specific mechanism by which SIN regulates the osteogenic differentiation of BMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al reported that SIN (20 and 40 mg/kg) impeded orthodontic tooth movement (OTM) and root resorption, enhanced alveolar bone structure, increased bone volume/total volume (BV/TV), and decreased trap-positive osteoclasts on the compression side. SIN at concentrations of 0.1 M and 0.5 M augmented ALP activity, facilitated the deposition of mineralized nodules, upregulated OPG, ALP, and RUNX, and diminished RANKL in periodontal ligament stem cells (PDLSCs) [ 220 ]. In the same year, it was published that SIN promoted skin flap survival.…”
Section: Other Activities Of Sinmentioning
confidence: 99%
“…Lactylation modification is known as a post‐translational regulatory mode, altering the protein stability 18 . Runt‐related transcription factor 2 (RUNX2) is an osteogenic gene, involving in the osteogenic differentiation of PDLSCs 19–21 . To date, it remains unclear whether SCO affects the lactylation‐mediated stability of RUNX2 in PDLSCs.…”
Section: Introductionmentioning
confidence: 99%
“… 18 Runt‐related transcription factor 2 (RUNX2) is an osteogenic gene, involving in the osteogenic differentiation of PDLSCs. 19 , 20 , 21 To date, it remains unclear whether SCO affects the lactylation‐mediated stability of RUNX2 in PDLSCs.…”
Section: Introductionmentioning
confidence: 99%